Role of XIST/miR‐29a/LIN28A pathway in denatured dermis and human skin fibroblasts (HSFs) after thermal injury. Issue 2 (7th September 2017) - Guo, Le; Huang, Xu; Liang, Pengfei; Zhang, Pihong; Zhang, Minghua; Ren, Licheng; Zeng, Jizhang; Cui, Xv; Huang, Xiaoyuan
Abstract : Denatured dermis is a part of the dermis in deep burn wound and has the ability to restore normal morphology and function. In our previous study, we revealed that miR‐29a downregulation in denatured dermis may help burn wound healing in the later phase, and further enhance type I collagen synthesis. LIN28A, a highly‐conserved RNA binding protein expressed during embryogenesis, plays roles in development, pluripotency, metabolism, as well as tissue repair in adults. In the present study, we investigated the functional roles of LIN28A in human skin fibroblasts (HSFs) and extracellular matrix (ECM), and the interaction between miR‐29a and LIN28A. In recent years, long non‐coding RNAs have been reported to play a key role in normal development and physiology, as well as in disease development. By using online tools, we screened out several candidate lncRNAs of miR‐29a, among which XIST was inversely regulated by miR‐29a. XIST, one of the first found cancer‐associated lncRNAs, has been frequently reported to play major role in several biological processes. Further, we evaluated the roles and mechanism of XIST in HSF proliferation, migration, and ECM synthesis. Through regulation of miR‐29a/LIN28A, XIST knockdown suppressed HSF proliferation, migration, and ECM synthesis. In denatured dermis tissues, XIST, and LIN28A expression was upregulated, miR‐29a expression was downregulated. Taken together, promoting XIST expression in denatured dermis, thus to inhibit miR‐29a and promote LIN28A expression, further promote HSF proliferation, migration, and ECM synthesis presents a promising strategy for denatured dermis repair. Abstract : Promoting XIST expression in denatured dermis, thus to inhibit miR‐29a and promote LIN28A expression, further promote HSF proliferation, migration and ECM synthesis presents a promising strategy for denatured dermis repair.